Faktor-Faktor yang Mempengaruhi Upaya Pengelolaan Sampah Limbah Medis di Rawat Inap Rumah Sakit Umum Kolonel Abundjani Bangko Tahun 2024 - Desvita S, Silvia Indah; Lestari, Tri (Universitas Batanghari Jambi, 2025)
The purpose of this study was to determine the factors that influence medical waste management in the Inpatient Unit of the Colonel Abundjani Bangko Regional General Hospital (RSU) in 2024 with a sample of 62 officers selected using the proportional random sampling method. The research method used a cross-sectional research design and the research variables were knowledge, attitudes and availability of facilities. The data collection technique used a questionnaire and analysis used the chi-square statistical test. The results showed that statistically only the availability of facilities for officers was associated with medical waste management efforts. Meanwhile, the knowledge and attitude variables for officers were not associated with medical waste management efforts in the Inpatient Unit of the Colonel Abundjani Bangko Regional General Hospital in 2024.